EXISTENCE, MOLECULAR DIAGNOSIS AND GENETIC VARIATION OF DIFFERENT ISOLATES OF ROOT – KNOT NEMATODES Meloidogyne spp. PARASITIZING CUCUMBER PLANTS - AMI, SULAIMAN NAIF; ABDULQAHAR, FADHILA IDRESS (Journal of Duhok University, 2023)
The findings indicated that the highest disease incidence (D.I.) was observed in autumn 2021 on cucumber plants grown in the greenhouses of Qustapa, with a rate of 87.5%. This was followed by a D.I. of 70% in the same location during spring 2022 and in the greenhouses of Daraband during autumn 2021.In both growing seasons in Daraband, and in Qustapa during Autumn 2021 more than 100 galls per root system were recorded, indicating a high level of infection and a highest root – knot index (5) . In contrast, no infection (D.I. 0.0%) was found in the greenhouses of Kamosak (Grd Goran) in both growing seasons and in Mastawa location during spring 2022. The results of soil analysis conducted in the surveyed locations revealed that the physical and chemical properties of the soil influence the movement and survival of  nematodes. Results of Molecular diagnosis using two universal primers included 10 Picomoles (pmol) of forward primer-TW81 (5’GTTTCCGTAGGTGAACCTGC-3’) and 10 pmol reverse primer-AB28 (5’ATATGCTTAAGTTCAGCGGGT-3’) identified four species of root-knot nematodes Meloidogyne spp., prevalent in cucumber greenhouses across the surveyed locations. namely. M. incognita, M. javanica, M. arenaria  and M. hapla and according to their genetic variation two races for each of the first three species were recorded for the first time by this technique